Pengaruh Metode Pembelajaran Outdoor Learning pada Materi Hidup Bersama Alam terhadap Kecerdasan Naturalistik Siswa Kelas III Sekolah Dasar: - - Ratih Prasetyaningrum; Wahyu Nugroho; Intan Susetyo Kusumo Wardhani (Mataram University, 2026)
This study was motivated by the suboptimal development of naturalistic intelligence among elementary school students, resulting from instruction that remains dominated by classroom-based activities and lacks direct interaction with the natural environment. The study aimed to determine the impact of the Outdoor Learning method—specifically focusing on the topic of